2022
DOI: 10.1186/s12886-022-02643-0
|View full text |Cite
|
Sign up to set email alerts
|

Functions of retinal astrocytes and Müller cells in mammalian myopia

Abstract: Background Changes in the retina and choroid blood vessels are regularly observed in myopia. However, if the retinal glial cells, which directly contact blood vessels, play a role in mammalian myopia is unknown. We aimed to explore the potential role and mechanism of retinal glial cells in form deprived myopia. Methods We adapted the mice form-deprivation myopia model by covering the right eye and left the left eye open for control, measured the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…There was also decreased peripheral retinal branchpoint density, along with a central increase in string vessels and retinal branchpoint density [17]. Supporting the existence of retinal glia alterations in myopia, increased GFAP expression and both astrocyte and Müller cell morphology changes have been demonstrated in a mouse model of myopia [18].…”
Section: Introductionmentioning
confidence: 77%
“…There was also decreased peripheral retinal branchpoint density, along with a central increase in string vessels and retinal branchpoint density [17]. Supporting the existence of retinal glia alterations in myopia, increased GFAP expression and both astrocyte and Müller cell morphology changes have been demonstrated in a mouse model of myopia [18].…”
Section: Introductionmentioning
confidence: 77%
“…Gliogenesis is one of the enriched GO entries ( Figure 3 A), which is indirectly supported by previous studies. It has been reported that the FDM retina tends to have increased numbers of astrocytes and Müller cells [ 52 ]. The secreted serine protease PRSS56 derived from Müller cells was shown to contribute to excessive ocular axial elongation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed according to our previously reported protocols (Zhang et al 2022 ). In brief, retinas were homogenized in RIPA buffer containing complete protease inhibitor cocktail (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…qRT-PCR was performed according to our previously reported protocols (Zhang et al 2022 ). Briefly, total RNA was extracted using TRIzol reagent (Takara, Japan).…”
Section: Methodsmentioning
confidence: 99%